ECONOMIC EVALUATION OF VITAMIN A AND D DEFICIENCY IN PAKISTAN - Abedullah; Abid Rashid; Sadia Aslam (Journal of University Medical & Dental College, 2015)
ABSTRACT: Prevalence of vitamin A & D deﬁciency (VAD, VDD) is very high in Pakistan. About 43 percent of population is vitamin A deﬁcient and sixty percent of population is vitamin D deﬁcient. VAD causes vision problems and increases the infections by reducing the immunity in adults. Considerable children are becoming blind due to its deﬁciency every year. VDD reduces the weight of bone tissue and leads to fractures. Both are contributing to cognition loss in children that leads to reduction in school attendance. These deﬁciencies in adults cause loss of working hours and reduce the physical productivity. Moreover, medication also consumes considerable proportion of income of poor families. Current study attempts to monetize the economic losses of these deﬁciencies by estimating the value of cognition and physical loss among children and adults due to VAD & VDD. We designed a questionnaire and interviewed 90 doctors all over the Pakistan to estimate medication costs due to prevalence of vitamin A & D deﬁciency among adult males and children up to age 14. We also accessed the online sources as well. Our result reveals that due to VAD & VDD, value of annual cognition losses in children are 8 and 6.4 per child, respectively. Values of annual physical productivity loss in adults are 3 and 5.6 per person, respectively but the cost of medication is estimated to be 37 and 41 per person per annum, respectively. If we aggregate these costs at national level then it amounts to 8.8 billion per annum which is quite high and demands for an immediate attention. In order to control these deﬁciencies, an appropriate intervention like supplementation or food fortiﬁcation is required